A Collectivist Philosophy of Trade Unionism - Cummings, Edward (Quarterly Journal of Economics, 1899)
Journal Article A Collectivist Philosophy of Trade Unionism Get access Edward Cummings Edward Cummings Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 13, Issue 2, January 1899, Pages 151–186, https://doi.org/10.2307/1882198 Published: 01 January 1899